Planejamento, execução e controle dos projetos da Copa do Mundo de 2014 no Brasil: estudo de caso Arena Pantanal em Cuiabá-MT - Brandão, Elaine Regina Correa (2012)
To perform the World Cup 2014, Brazil seeks economic and financial feasibility of investments in projects. However, this whole organization to the world depends on the efficiency and effectiveness in the management of projects of the host cities; projects that are planned and executed by the three tiers of government (Federal, State and Municipal). In this context, this study aims to identify the structure of the Planning, Execution and Control of projects from the World Cup 2014 in Brazil, Cuiabá, capital of Mato Grosso. So, we defined the theoretical framework based on the concepts of renowned authors who talk about relevant aspects: Planning, Implementation and Control, especially in the public sector for the management of projects. Regarding methodology, we chose to study with a qualitative approach exploratory and descriptive, using a case study on the design of Arena Pantanal held at Secretária Extraordinária da Copa (SECOPA) in Cuiabá-MT, where we performed the data collection, document analysis and interviews. To make the analysis of results, we used additional data obtained from a secondary site and available in the SECOPA. Through them, we conclude that the World Cup 2014 tends to project the host city of Cuiabá-MT, where the design of the master plan of the project was based in order to meet the budget Laws prioritizing the needs of society and involving large investments in infrastructure, such as the construction of Arena Pantanal Multiuso. Therefore, the SECOPA has been working with the challenges, risks and constraints (expropriations, fundraising, lawsuits etc..). Remarkable, also, the many opportunities (increase in employment generation, income, consumption, projecting the city as a tourist attraction, urban mobility), besides adding other direct and indirect benefits, expressive and positively affecting the socioeconomic development of Cuiabá- MT